2017
DOI: 10.1002/ejlt.201700212
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Polymeric Nanoparticles From Castor Oil Derivatives via Thiol‐Ene Miniemulsion Polymerization

Abstract: Biocompatible polymeric nanoparticles are obtained via thiol-ene polymerization of a biobased monomer in miniemulsion. The α,ω-diene-diester monomer is synthesized through esterification reaction of a glycerol derivative, namely 1,3-propanediol, with 10-undecenoic acid, a long-chain diene carboxylic acid. In order to investigate how different monomeric structures behave toward thiolene polymerization in miniemulsion, two types of thiols are investigated: 1,4-butanedithiol and 2-mercaptoethyl ether. Poly(thioet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Repetition with 1.0 wt.% DMPA and otherwise similar conditions proceeded quantitatively in 5 min. These results agreed with previous studies that indicated photoreactions are dramatically accelerated when PI are employed (Alagi et al, ; Cardoso et al, ; Claudino et al, ; Northrop and Coffey, ; Samuelsson et al, ; Unverferth and Meier, ). Consequently, all ensuing photochemical reactions were conducted with 1.0 wt.% DMPA.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Repetition with 1.0 wt.% DMPA and otherwise similar conditions proceeded quantitatively in 5 min. These results agreed with previous studies that indicated photoreactions are dramatically accelerated when PI are employed (Alagi et al, ; Cardoso et al, ; Claudino et al, ; Northrop and Coffey, ; Samuelsson et al, ; Unverferth and Meier, ). Consequently, all ensuing photochemical reactions were conducted with 1.0 wt.% DMPA.…”
Section: Resultssupporting
confidence: 93%
“…Subsequent treatment with isocyanate gave a polyurethane (Lluch et al, ). Polyesters were also prepared via reaction of alkyl 10‐undecenoates with various thiols (Cardoso et al, ; Turunc and Meier, ), and polyamides were synthesized from a thiolactone derivative of UDA (Goethals et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility and bioactivity of SACPNs are typically investigated by MTT assay and hemolysis test in vitro. Moreover, intraperitoneally administration into mouse is used to investigate the acute toxicity in vivo and biodistribution test is also applied to identify whether it has good biocompatibility and bioactivity (Cardoso et al, 2018;Nosrati et al, 2018;Yuan et al, 2018). Among all these techniques, MTT assay is the primary one that is typically used as the first test to investigate the biocompatibility and bioactivity of SACPNs.…”
Section: Advanced Drug Delivery Systemsmentioning
confidence: 99%
“…[24][25][26][27][28] Thiol-ene polymerization in miniemulsion has only been reported after 2014 in works describing the synthesis of nanoparticles comprised of linear polymers. 22,29,30 The synthesis of nanoparticles via thiol-ene miniemulsion polymerization allows the development of different kinds of material that could not be straightforwardly produced through other polymerization techniques, such as waterborne polyesters, some works were able to synthesize high molecular poly(thioetherester) (PTEE) via thiol-ene polymerization in miniemulsion 22,30 ; in addition, thiol-ene polymerization is a versatile technique that can be applied to the polymerization of biobased monomers from vegetable oils containing double bonds that are less reactive toward traditional free radical polymerization. 31,32 Also, in the past few years this click chemistry reaction has drawn attention to its use in the production of biomaterials, especially PTEE which is biodegradable 33,34 and no cytotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Also, in the past few years this click chemistry reaction has drawn attention to its use in the production of biomaterials, especially PTEE which is biodegradable 33,34 and no cytotoxic. 30 Therefore, this work aims to synthesize nanocomposites suitable to biomedical applications by encapsulating MNPs in situ via thiol-ene polymerization in miniemulsion and to utilize the PTEE/MNPs-oleic acid (OA) hybrid nanoparticles for hyperthermia treatment of tumors.…”
Section: Introductionmentioning
confidence: 99%